Perencanaan dan Perancangan Wana Wisata Waduk Kedungombo di Wonoharjo Kabupaten Boyolali dengan Konsep Waterfront - Pawitra Sari; Abito Bamban Yuuwono; Dian Dianti Avoress; Eddy Shaka Saputra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
Boyolali Regency is one of the regencies in Central Java, which has a very rapid industrial development, and Boyolali Regency itself has many natural resources, including oil mines, teak forests, onyx stone mines, as well as abundant agricultural and plantation products. Meanwhile, the development of tourism in Boyolali is no less important. Many areas have their own tourism attractions, including Boyolali which has a lot of natural potential that is used as tourism. Therefore, the Planning and Design of the Kedungombo Reservoir Reservoir in Boyolali is very important, besides the Waterfront concept approach is an attraction for the Boyolali community to move forward. The application of the Waterfront Concept in Boyolali is marked by several forms and symbols that contain elements of Waterfront. One of the concepts inherent in Boyolali is the Kedungombo Reservoir, because in ancient times the reservoir was a means of supporting the economic activities of the Boyolali people, the Kedungombo Reservoir in Boyolali has also become a center for the development of fish farming at the national level. So on that basis the Kedungombo Reservoir in Boyolali became the main concept of tourism and then packaged through the development of modern times with the concept of Waterfront City. With the Kedungombo Reservoir Tourism Wana, Boyolali's achievement to increase the Regional Income Budget (APD) can be achieved.